Novel hydroxycinnamamide from morpholine and pyrrolidine: Synthesis, characterization, docking study, and anticancer activity against P388 leukemia murine cells - Firdaus, Nunuk Hariani Soekamto, Syadza Firdausiah, Herlina Rasyid&, Nur Asmi, Muzdalifah Waelulu (Journal of Applied Pharmaceutical Science, 2021)
This study aimed to synthesize N-(p-coumaroyl)morpholine (6a), N-caffeoylmorpholine (6b), N-(p-coumaroyl) pyrrolidine (7a), and N-caffeoylpyrrolidine (7b) from p-coumaric and caffeic acid through acetylation, chlorination, amidation, and deacetylation reactions. The characterization of these compounds was committed by Fourier transform infra-red and NMR spectroscopy, while the anticancer activity was studied against murine leukemia P388 cells. Compounds 6a, 6b, and 7b were found to have remarkable anticancer activity with IC50 values ≤ 50 μg/ml. Furthermore, 6b performed very active anticancer activity with IC50 of 1.48 μg/ml. The molecular docking study of compound 6b against the Top1 protein receptor showed the presence of hydrogen bond interactions on Asn722 and Thr718 amino acid residue. Thus, these compounds are promising candidates as anticancer agents.
Keywords: Amidation, caffeic acid, cytotoxic, molecular docking, p-coumaric acid.